Chat with our AI personalities
Look at it this way: 1y2 is also shown as 1y x 1y So. if you now replace the 1y for 3ft then you get this: 3ft x 3ft And 3 x 3 = 9 3ft x 3ft = 9ft2 equal to 1y x 1y = 1y2 Hope this helps
The algebraic expression of: -x-1y has the same value as -x-y
When you have a variable by itself either it be x or y there is always an invisible place holder before it. So a normal "y" would be "1y". So when you put 1y + 1y you get 2y.
1+1+x+x+x+y+y=2+3x+2y
y = 2x + 1 1. Make a table: x = -2; y = -3y = 2x + 1y = 2(-2) + 1 = -4 + 1 = -3 x = -1; y = -1y = 2x + 1y = 2(-1) + 1 = -2 + 1 = -1x = 0; y = 1y = 2x + 1y = 2(0) + 1 = 0 + 1 = 1 x = 1; y = 3y = 2x + 1y = 2(1) + 1 = 2 + 1 = 3 x = 2; y = 5y = 2x + 1y = 2(2) + 1 = 4 + 1 = 5 2. Plug the points (-2, -3), (-1, -1), (0, 1), (1, 3), and (2, 5) in a xy-coordinate system. 3. Draw a line which passes through those points. Thus, the line drawn is the graph of the function y = 2x + 1